Engineered 3D Cardiac Fibrotic Tissue to Study Fibrotic Remodeling. Issue 11 (12th May 2017) - Sadeghi, Amir Hossein; Shin, Su Ryon; Deddens, Janine C.; Fratta, Giuseppe; Mandla, Serena; Yazdi, Iman K.; Prakash, Gyan; Antona, Silvia; Demarchi, Danilo; Buijsrogge, Marc P.; Sluijter, Joost P. G.; Hjortnaes, Jesper; et al.
Abstract : Activation of cardiac fibroblasts into myofibroblasts is considered to play an essential role in cardiac remodeling and fibrosis. A limiting factor in studying this process is the spontaneous activation of cardiac fibroblasts when cultured on two‐dimensional (2D) culture plates. In this study, a simplified three‐dimensional (3D) hydrogel platform of contractile cardiac tissue, stimulated by transforming growth factor‐β1 (TGF‐β1), is presented to recapitulate a fibrogenic microenvironment. It is hypothesized that the quiescent state of cardiac fibroblasts can be maintained by mimicking the mechanical stiffness of native heart tissue. To test this hypothesis, a 3D cell culture model consisting of cardiomyocytes and cardiac fibroblasts encapsulated within a mechanically engineered gelatin methacryloyl hydrogel, is developed. The study shows that cardiac fibroblasts maintain their quiescent phenotype in mechanically tuned hydrogels. Additionally, treatment with a beta‐adrenergic agonist increases beating frequency, demonstrating physiologic‐like behavior of the heart constructs. Subsequently, quiescent cardiac fibroblasts within the constructs are activated by the exogenous addition of TGF‐β1. The expression of fibrotic protein markers (and the functional changes in mechanical stiffness) in the fibrotic‐like tissues are analyzed to validate the model. Overall, this 3D engineered culture model of contractile cardiac tissue enables controlled activation of cardiac fibroblasts, demonstrating the usability of this platform to study fibrotic remodeling. Abstract : Engineered 3D cardiac fibrotic tissue is fabricated by using a cardiac cell‐laden 3D hydrogel‐platform which is used to create a physiologically relevant in vitro platform to control the activation of cardiac fibroblasts as they are induced into cardiac myofibroblasts. By the exogenous addition of a pro‐fibrotic transforming growth factor‐β1, the heart tissues reveal de novo expression of several cardiac fibrosis markers.